Concentration level of arsenic in agricultural soil and surface water used for irrigation in Bukuru, JOS- south LGA of plateau state, Nigeria - J.D, Dodo; C.O, Akinola; E., Ogah; S. J., Salami (International Journal of Advanced Chemistry, 2021)
Arsenic concentration of agricultural soil and surface water used for irrigation were surveyed in two abandoned mining sites of Jos South Local Government Area. DB-Zang and Dorowa total dissolved solid, total hardness, electrical conductivity, temperature and pH of the agricultural soil and surface water were determined according to standard procedure. Result indicates that Total dissolve solids in W1 was 156Â±2.00mg/L and for W2 (160Â±2.00mg/L), total hardness W1 (35.20Â±4.70mg/L) and W2 (44.67Â±4.70mg/L), electrical conductivity for W1 was 0.240Â±0.189Âµs/cm and W2 was 0.120Â±0.189Âµs/cm ,electrical conductivity for S1 (0.49Â±0.16Âµs/cm), S2 (0.17Â±0.16Âµs/cm), temperature for both water was 28.00Â±0.00oC for soil are 18.00Â±0.00 o C, pH for W1 (7.10Â±0.05) and W2 (7.20Â±0.05), pH for S1 (6.90Â±0.15) S2 ( 6.60Â±0.15). The concentration of Arsenic in soil L2 is14.00Â±0.70Âµg/kg which is in agreement with WHO recommended level of Arsenic in soil and for L1 257.00Â±120.00Âµg/kg which is not in agreement with the WHO recommended level of arsenic, while in water for L1 was 3.00Â±0.50Âµg/L which is not in agreement with the WHO recommended level of arsenic and L2 was 48.00Â±0.70Âµg/L which is not in agreement with the WHO recommended level of arsenic. The cultivation of food crops in those areas are not recommended. Â Â Â